Pengaruh Penggunaan Software Swishmax dengan Pendekatan Culturally Responsive Teaching (CRT) terhadap Minat Belajar Matematika Siswa - Prabowo, Danang Bagus; Hidajat, Djatmiko; Wulandari, Andhika Ayu (Jurnal Simki Pedagogia, 2025)
This study aims to determine whether the use of Swishmax software through the Culturally Responsive Teaching (CRT) approach has an effect on students' interest in learning mathematics. This study uses an experimental method in a quantitative approach. The population in this study was grade XI students, with samples selected using the random sampling method. Data collection was carried out through questionnaires and documentation. Data analysis techniques include calculating the average score, standard deviation, normality test, homogeneity test, and hypothesis test. The analysis prerequisite test was carried out through the Liliefors normality test, then continued with the F homogeneity test. For hypothesis analysis, the t-test (Independent t-Test) was used through a significance level of 5%. The results of the study show that if the t-count value is 2.62019, the t-table value at a significance level of 5% at df = 62 is 1.6698. From these data, t_count> t_table was obtained so that it can be concluded that there is an impact of using Swishmax Software through the Culturally Responsive Teaching (CRT) approach on students' interest in learning Mathematics.